2017
DOI: 10.1002/2016jb013758
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the BASALT model for simulating off‐axis hydrothermal circulation in oceanic crust

Abstract: Fluid recharge and discharge between the deep ocean and the porous upper layer of off‐axis oceanic crust tends to concentrate in small volumes of rock, such as seamounts and fractures, that are unimpeded by low‐permeability sediments. Basement structure, sediment burial, heat flow, and other regional characteristics of off‐axis hydrothermal systems appear to produce considerable diversity of circulation behaviors. Circulation of seawater and seawater‐derived fluids controls the extent of fluid‐rock interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…We did not address the effect of the thickness of the aquifer on the resulting flow since this has already been investigated in previous studies (Farahat et al., 2017; Lauer et al., 2018; Stein & Fisher, 2003; Winslow et al., 2016). Those studies found that outcrop‐to‐outcrop flow through a thicker aquifer causes enhanced siphon flow rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not address the effect of the thickness of the aquifer on the resulting flow since this has already been investigated in previous studies (Farahat et al., 2017; Lauer et al., 2018; Stein & Fisher, 2003; Winslow et al., 2016). Those studies found that outcrop‐to‐outcrop flow through a thicker aquifer causes enhanced siphon flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have successfully performed numerical simulations of outcrop‐to‐outcrop flow in 2‐D (Anderson et al., 2012; Davis et al., 1997; Farahat et al., 2017; Hutnak et al., 2006; Stein & Fisher, 2003) and 3‐D (Lauer et al., 2018; Price et al., 2022; Winslow & Fisher, 2015; Winslow et al., 2016). These models converge on the prediction that outcrop‐to‐outcrop flow requires high aquifer permeabilities >10 −13 m 2 (Fisher, Davis, et al., 2003; Winslow et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the fault model seems appropriate and straightforward for the Pescadero vents, it does seem to be the exception compared to other known sediment‐hosted vent fields in the Pacific, which require entirely different boundary conditions than those observed in the Pescadero Basin. Convection at ridge flanks usually is sealed off from the ocean by a layer of fine‐grained sediments of the deep ocean which typically have a permeability much lower than that of the upper volcanic crust resulting in little fluid exchange through seafloor sediments (e.g., Farahat et al., 2017; Fisher & Wheat, 2010). In this model, seamounts play a fundamental role in facilitating the exchange of fluids, heat, and solutes between the oceanic lithosphere and the overlying ocean by providing pathways for discharge and recharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fault model seems appropriate and straightforward for the Pescadero vents, it does seem to be the exception compared to other known sediment-hosted vent fields in the Pacific, which require entirely different boundary conditions than those observed in the Pescadero Basin. Convection at ridge flanks usually is sealed off from the ocean by a layer of fine-grained sediments of the deep ocean which typically have a permeability much lower than that of the upper volcanic crust resulting in little fluid exchange through seafloor sediments (e.g., Farahat et al, 2017;Fisher & Wheat, 2010). In this model, seamounts play a fundamental role in facilitating the exchange of fluids, heat, and solutes between the oceanic lithosphere and the overlying ocean by providing pathways for discharge and recharge.…”
Section: Comparison With Other Vent Fields In the Pacificmentioning
confidence: 99%